Mineralogical, textural and liberation studies of tungsten ore deposits of Chitral, Khyber Pakhtoon Khwa Province, Pakistan - Mehmood, Rashid; Bhatti, Muhammad Arif; Butt, Kashif; Kazmi, Kamarn Raza; Akram, Adnan (Journal of Nepal Geological Society, 2014)
An investigation was undertaken on tungsten ore deposits of Chitral area, Khyber Pakhtoon Khawa Province, Pakistan for its evaluation and subsequently selection of a suitable process for its beneficiation. The ore deposit was evaluated by microscopy, petrography, X-ray diffractometry and chemical analysis. The principal mineral constituents present in the ore were identified. The textural characteristics such as crystal size, shape and mutual arrangement of the component minerals in the ore body were investigated. The degree of liberation of valuable mineral was studied by grain mounts. Mineralogy, texture and liberation studies reveal that this ore is amenable to beneficiation by froth flotation technique.